Centrality and content creation in networks: The case of German Wikipedia - Michael E. Kummer; Marianne Saam; Iassen Halatchliyski; George Giorgidze (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
When contributing content on large online platforms, producers of user-generated content have to decide where to contribute. On a complex and dynamic platform like Wikipedia, this decision is expected to depend on the way the content is organized. We analyse whether the hyperlinks on Wikipedia channel the attention of producers towards more central articles. We observe a sample 7,635 articles belonging to the category 'Economics' on German Wikipedia over 153 weeks and measure their centrality both within this category and in the network of over one million German Wikipedia articles. Our analysis reveals that an additional link from the observed category is associated with around 140 bytes of additional content and with an increase in the number of authors by nearly 0.5. Moreover we observe that the rate of content generation increases notably when previously unlinked articles get connected to the main cluster in the category.
Keywords: L14; D83; 330; Wikipedia; network position; user-generated content; hyperlinks; Social Software; Internet; Web 2.0